The Investigation of ICT Needs in the Learning Process of Digital Natives - Jean Elikal Marna; Menik Kurnia Siwi; Oknaryana Oknaryana (Universitas Negeri Malang, 2020)
The study aims to investigate and analyze the needs of information and communications technology (ICT) in the learning process of digital-native students of the Faculty of Economics, Universitas Negeri Padang in Indonesia. The data were collected by using a structured questionnaire, and it was analyzed undergoing the descriptive method. The results of this study indicated that the majority of students use technology in the learning process, such as smartphone and laptop all the time. In general, students prefer using WhatsApp and e-learning to support their learning activity. The adoption of technology is affected by easiness to use and provide a piece of fast and comprehensive information. Therefore, they believe that the use of technology is relatively high within the learning process of the digital natives that technology integration in education is highly demanded.